RESOURCE RATIONALIZATION FOR LARGE SCALE SOFTWARE PROJECTS BY REDUCING RISKS - SHAHZAD, BASIT (2015)
Risks are a common phenomenon in software development and have negative impact on the development process. A software process is considered mature, if it can identify. prioritize and mitigate the risk factors before they have become harmful. This research is focused to identify some core components of a model that ultimately reduces the risks and improves the resource allocation for software projects. The research study identifies prominent risk factors. project factors and gages the impact of all identified risk factors along with their probability. The association among the risk factors and project factors is established in result of an elaborated study. This research consequently determines that how a model can be developed, implemented and tested to ensure that by applying that model the risks are reduced I eliminated and the resource allocation is improved.